Music as a Strategic Instrument for Enhancing Social Coherence - A Comprehensive Need - Ngobeni, Nyiko Condry; Bopape, Maishe Harry (Universitas Negeri Semarang, 2024)
This paper explores the strategic role of music in enhancing social coherence within organisations and communities. Drawing from insights into psychology, organisational behaviour, and sociology, we investigate how music catalyses fostering collaboration, strengthening relationships, and promoting inclusivity. By integrating music into various facets of organisational life, including branding strategies and decision-making processes, organisations can create environments that entertain, inspire, and unite individuals. Organisations can communicate values, evoke emotions, and establish a sense of belonging among stakeholders through music. Whether through the selection of background music in the workplace, the incorporation of music into marketing campaigns, or the use of music-based activities in team-building exercises, the strategic deployment of music can significantly impact social dynamics and organisational culture. Embracing music as a strategic tool enables organisations to create inclusive environments where diverse perspectives are valued, and individuals feel connected and supported. By identifying and leveraging music's transformative potential, organisations can cultivate cohesive, interconnected societies that thrive on collaboration and mutual respect. This study highlights the importance of integrating music into strategic initiatives to foster social cohesion and build resilient communities.